2019
DOI: 10.1080/0284186x.2019.1674452
|View full text |Cite
|
Sign up to set email alerts
|

Benchmarking single-arm studies against historical controls from non-small cell lung cancer trials – an empirical analysis of bias

Abstract: Background: Recent trials of novel agents in 'rare' molecular subtypes of non-small cell lung cancer (NSCLC) have used single-arm trial designs and benchmarked outcomes against historical controls. We assessed the consistency of historical control outcomes using docetaxel data from published NSCLC randomized controlled trials (RCTs). Material and methods: Advanced NSCLC RCTs including a docetaxel monotherapy arm were included. Heterogeneity in tumor objective response rates (ORRs), progression-free survival (P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…27 Drift due to improvements in care over time is also an important concern in practice. In a meta-analysis by Snyders et al, 33 who looked at 63 trials of docetaxel in lung cancer (enrolling over 10,000 patients), it was found that outcomes improved each year by a mean of 0.3% in objective response rate (ORR), 0.5% for progression-free survival (PFS), and 0.9% in OS. These changes over time imply that historical data that are more than say 10 years old for docetaxel in this indication should be avoided.…”
Section: Discussionmentioning
confidence: 99%
“…27 Drift due to improvements in care over time is also an important concern in practice. In a meta-analysis by Snyders et al, 33 who looked at 63 trials of docetaxel in lung cancer (enrolling over 10,000 patients), it was found that outcomes improved each year by a mean of 0.3% in objective response rate (ORR), 0.5% for progression-free survival (PFS), and 0.9% in OS. These changes over time imply that historical data that are more than say 10 years old for docetaxel in this indication should be avoided.…”
Section: Discussionmentioning
confidence: 99%
“…Comparative effectiveness analyses incorporating ECs are at risk of inherent biases associated with observational data. [52][53][54][55][56][57][58][59][60] Common types of biases include selection bias, information bias, and time-related bias (Table 1). These biases should be considered early when the study is conceptualized and comprehensively addressed in the SAP.…”
Section: Considerations For Potential Biases and Confoundingmentioning
confidence: 99%
“…An additional issue with ORR based drug approval is the lack of a control arm since these are usually from single arm trials. In the absence of a control, comparative analysis and cost-effectiveness analysis become impossible to inform HTA decisions and HTA agencies will have to rely on ORR from historical control which is fraught with several biases [18,19]. Even then, the effect on survival remains unknown.…”
Section: Key Pointsmentioning
confidence: 99%